2020
DOI: 10.1016/j.kint.2019.09.032
|View full text |Cite
|
Sign up to set email alerts
|

The circadian clock is disrupted in mice with adenine-induced tubulointerstitial nephropathy

Abstract: Sleep disorders are prevalent in chronic kidney disease patients, although the underlying mechanisms are not understood. The current study demonstrates that adenine-induced tubulointerstitial nephropathy disrupted the circadian system both centrally and in peripheral organs. Clock mutant mice were also more vulnerable to the effects of adenine. These findings aid the understanding of sleep disturbances in adenine phosphoribosyltransferase deficiency, a rare inherited metabolic disorder that leads to the accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 44 publications
(51 reference statements)
5
40
0
Order By: Relevance
“…Thus, Per1 KO mice develop non-dipping hypertension under conditions of sodium retention while Clock KO mice lose the circadian rhythmicity in urinary water and electrolyte excretion and develop more severe kidney fibrosis upon ureteral obstruction but were protected from kidney fibrosis driven by sodium retention conditions [14]. Additionally, Clock mutants had some features suggesting increased severity of adenine-induced CKD, such as higher blood pressure and expression as some gelatinase genes, but there were no differences in kidney fibrosis or serum creatinine [21]. Bmal1 KO mice develop accelerated aging, hypotension and a non-dipping blood pressure pattern and lose the circadian variations in interstitial medullary osmolarity suggesting a role of circadian clocks in the control of urine volume beyond dietary clues [14,22].…”
Section: Biological Rhythmsmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, Per1 KO mice develop non-dipping hypertension under conditions of sodium retention while Clock KO mice lose the circadian rhythmicity in urinary water and electrolyte excretion and develop more severe kidney fibrosis upon ureteral obstruction but were protected from kidney fibrosis driven by sodium retention conditions [14]. Additionally, Clock mutants had some features suggesting increased severity of adenine-induced CKD, such as higher blood pressure and expression as some gelatinase genes, but there were no differences in kidney fibrosis or serum creatinine [21]. Bmal1 KO mice develop accelerated aging, hypotension and a non-dipping blood pressure pattern and lose the circadian variations in interstitial medullary osmolarity suggesting a role of circadian clocks in the control of urine volume beyond dietary clues [14,22].…”
Section: Biological Rhythmsmentioning
confidence: 98%
“…In murine adenine-induced CKD, in vivo disrupted timekeeping could be dissociated in vitro into a suprachiasmatic nucleus pacing, which remained uncompromised, and a kidney clock that became a less robust circadian oscillator with a longer period, suggesting that the kidney contributes to overall circadian timekeeping and that there is local kidney disruption of circadian rhythms during CKD [47]. By contrast, in vivo exploration of mice with adenine-induced CKD disclosed low amplitude PER2:luciferase rhythms in their central suprachiasmatic nucleus circadian clock and in intact kidney, liver, and submandibular gland, as well as altered expression patterns of circadian genes including canonical clock genes and kidney genes such as Hif, Aqp2, and V2r [21]. Overall, these results point to interference of peripheral clocks with the central clock in CKD.…”
Section: Chronodisruption In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, retinol-induced expression of CLOCK protein may be dependent on the levels of STRA6. The altered expression of clock genes is also observed in other CKD model animals 25 . The expression rhythms of clock genes were attenuated in the kidneys of mice fed an adenine-containing diet.…”
Section: Discussionmentioning
confidence: 73%
“…Many previous studies report the pathological states of Clk/Clk mice 15 , 22 , 23 . We and others investigated how the mutation of Clock gene affects the pathology of CKD 24 , 25 . In characterizing the hepatic metabolic status and inflammatory response of wild-type mice with 5/6 nephrectomy (5/6Nx), an experimental model of CKD characterized by the slow development of glomerulosclerosis, vascular sclerosis, tubulointerstitial fibrosis, and renal inflammation, we found that the abnormal increase in serum retinol levels in 5/6Nx wild-type mice induces the activation of caspase and apoptotic cell death in the kidney, further exacerbating the pathologies of CKD 26 .…”
Section: Introductionmentioning
confidence: 99%